La responsabilité civile délictuelle des municipalités en matière d'entretien des rues et des trottoirs pendant l'hiver - McNicoll, Micheline (Les Cahiers de droit, 1982)
An exhaustive review of our case law is required for a proper understanding of municipalities' civil liability for offences and quasi-offences. It appears indeed that there is no other alternative since, on one hand, the legislator is mute on number of important relevant questions and, on the other hand, municipalities, are governed by rules of public law. Our review covering a period of about eighty years, contains an analysis of the three « schools of thought » that succesively exerciced considerable influence upon our court decisions. The different « schools of thought » naturally emerged from the constant opposition of public and private law divided by a boundary line subject to fluctuation.